2016
DOI: 10.15185/izawol.260
|View full text |Cite
|
Sign up to set email alerts
|

Performance measures and worker productivity

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 13 publications
(47 reference statements)
0
33
0
5
Order By: Relevance
“…In a more systematic approach, the measurements made rely on the assumption that companies must base their strengths in its financial profitability and productivity (Guo, Hotchkiss, & Song, 2011;Jain & Kini, 1994;Kaplan, 1989), presenting an effective commercial performance (Wiggins & Gibson, 2003) and leveraging their innovation on tax credits and grants provided to support innovation and technological leadership (Howell, 2017) at national and European level. Further measurement can be done so that it is verified that ensuring that each job created presents an added value to the entrepreneurial process (Sauermann, 2016) with reasonable salaries (Botti, 2013) and with an external market orientation (Rose & Shoham, 2002).…”
Section: Designmentioning
confidence: 99%
“…In a more systematic approach, the measurements made rely on the assumption that companies must base their strengths in its financial profitability and productivity (Guo, Hotchkiss, & Song, 2011;Jain & Kini, 1994;Kaplan, 1989), presenting an effective commercial performance (Wiggins & Gibson, 2003) and leveraging their innovation on tax credits and grants provided to support innovation and technological leadership (Howell, 2017) at national and European level. Further measurement can be done so that it is verified that ensuring that each job created presents an added value to the entrepreneurial process (Sauermann, 2016) with reasonable salaries (Botti, 2013) and with an external market orientation (Rose & Shoham, 2002).…”
Section: Designmentioning
confidence: 99%
“…20 For the sake of economy, we do not include these results, but they are available upon request. 21 Although the Internet and FedEx have partially replaced mail recently, letter delivery by the postal service is still dominant (Guislain 2004;Chong et al 2014). office for private gain") applies exclusively to the public sector and reflects its efficiency and productivity (Sauermann 2016). Second, it has been shown that there is high correlation between labor rigidity in the private and public sectors in many countries.…”
Section: Labor Rigidity In the Public Sector: Discussionmentioning
confidence: 99%
“…As mentioned earlier by Sauermann (2016) [10], productivity is the measure of output per unit of input. Meanwhile, Jorgenson et al (2007) [11] stated that the difference between total real output product and total real factor input defines productivity.…”
Section: Literature Review 21 Productivity In Oil and Gas Industrymentioning
confidence: 99%
“…Productivity, in technical term, is the measure of output per unit of input [3]. Productivity involves the efficiency of the usage of labor, resources, capital and many others.…”
Section: Introductionmentioning
confidence: 99%